Stowarzyszenie Rodzin Wielokulturowych – organizacja pozarządowa reprezentująca interesy osób odmiennych kulturowo - Sowa-Behtane, Ewa (Kultura-Społeczeństwo-Edukacja, 2018)
The article attempts to shows that in the era of post-modernity, the ethnically, racially, religiously, culturally or nationally mixed marriages are more and more frequent phenomenon, contributing to the emergence of new types of cultural identity. The degree of cultural difference determines the number of problems which occur between partners. National, religious, linguistic and cultural differences can affect both positively and negatively functioning multicultural families. The main context of this article is the activity of Multicultural Families Association, which was formed in the aftermath of diagnosis multicultural families living in Krakow. The Association responds to the needs of these families.